Structural snapshots of the rearrangement of the bis(di-tert-butyl-aminophenyl)amine pincer ligand in the presence of transition metal ions. Issue 33 (25th July 2018) - Leconte, N.; Baptiste, B.; Philouze, C.; Thomas, F.
Abstract : The ligand undergoes N–N and C–N bond formations in the presence of redox-active transition metal ions, in air and coordinating solvents. Abstract : The bis(di- tert -butyl-aminophenyl)amine ligand H3 L N, N, N was reacted with Mn(ii ), Co(ii ), Fe(iii ) and Cu(ii ) salts in air. The ligand undergoes oxidative transformations, which involve intra and intermolecular C–N and N–N bond formations. A rare aromatic C–N bond cleavage leading to a C–O bond has also been observed.